2003
DOI: 10.1177/153331750301800610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal-assisted therapy on agitated behaviors and social interactions of older adults with dementia

Abstract: The effects of a therapeutic recreation intervention using animal-assisted therapy (AAT) on the agitated behaviors and social interactions of older adults with dementia were examined using the Cohen-Mansfield Agitation Inventory and the Animal-Assisted Therapy Flow Sheet. In a pilot study, 15 nursing home residents with dementia participated in a daily AAT intervention for three weeks. Results showed statistically significant decreases in agitated behaviors and a statistically significant increase in social in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
152
1
18

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(180 citation statements)
references
References 12 publications
9
152
1
18
Order By: Relevance
“…Earlier studies have shown the effect of AAI on social, behavioural, psychological, and physiological outcomes, such as increased social behaviour (12)(13)(14)(15), decreased depression (19,20,63), increased mood (64), decreased agitation (10,17), and physiological outcomes that might reduce restlessness (for other studies, see the review by Beetz et al (58)). These factors are all linked to fall prevention (65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have shown the effect of AAI on social, behavioural, psychological, and physiological outcomes, such as increased social behaviour (12)(13)(14)(15), decreased depression (19,20,63), increased mood (64), decreased agitation (10,17), and physiological outcomes that might reduce restlessness (for other studies, see the review by Beetz et al (58)). These factors are all linked to fall prevention (65).…”
Section: Discussionmentioning
confidence: 99%
“…Animalassisted activities (AAAs) are one type of AAI and include, for example, dogs and their handlers who visit for 'meet-and-greet' activities (11). Most studies of AAIs have focused on the interventions' impacts on social outcomes (12)(13)(14)(15), behavioural and psychological outcomes (16)(17)(18)(19)(20), and physiological outcomes (21-23), many of which are regarded as risk factors associated with falls. However, there are fewer studies of the effect of AAIs on performance-based physical outcomes and the results from these studies are inconsistent (19,24).…”
Section: Introductionmentioning
confidence: 99%
“…Following extensive literature review, we found no study to date that investigated the use of AAT for persons with stroke or aphasia. Despite the lack of research in AAT for persons with aphasia, numerous studies have been performed on the effects of AAT on other adult populations, such as residents of nursing homes [9][10][11][12]; patients in acute-care hospitals [13][14][15][16]; patients in intensive care units [17]; and adults with spinal cord injury [18], dementia [19][20], depression [21], psychiatric disorders [21][22][23], and schizophrenia [24][25][26].…”
Section: Animal-assisted Therapymentioning
confidence: 99%
“…Discussing the dog can help the patient open up by triggering positive memories or pleasant feelings [11]. Communication interventions and an optimistic atmosphere can have a positive impact on QoL and can also assist nursing staff in different caring situations [19] and social interactions [9,11,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The dogs are used with positive results in healthcare settings in relation to people with dementia or psychiatric disorders [3,4]. A growing scientific evidence base indicates that DAIs can reduce behavioral and psychological symptoms and/or improve quality of life (QoL) in people with dementia [5][6][7][8][9][10][11]. Moreover, the use of therapy dogs can possibly slow down the progression of cognitive impairment in patients with early stage or mild Alzheimer's disease [12].…”
Section: Introductionmentioning
confidence: 99%